Periodontal surgery for clinical crown augmentation (Research, Society and Development, 2021)
Introduction: Beginning in 1912, a treatment from the gingivectomy era to reduce supraosseous periodontal pockets and removal of gingival hyperplasia is currently one of the most sought after procedures for smile correction. Gingivoplasty was suggested by Goldman in 1950, making it clear, therefore, that both gingivectomy and gingivoplasty are guided by the same technical sequence, both are an aesthetic resective surgery improving the physiological reestablishment of the biological space. Methodology: This is a descriptive research. Results and Discussion: According to the literature, in 1979, gingivectomy was defined as an excision of soft tissue from the pathological periodontal pocket. Widmam (1918) also called it the “original widmam flap” where to establish a new physiology for the alveolar bone, the author learned the flap technique to eliminate periodontal pocket. Kronfeld (1935) concluded that in gingivectomy it could not expose the bone tissue, and this procedure is indicated to remove the hyperplastic gingival tissue, being also able to remove the inserted, marginal and papillary gingiva (Penteado, 2015). Final Considerations: It is concluded that, given the above, gingivoplasty is similar to gingivectomy, however, with differences that in the first mentioned, the objective would be that the gingiva becomes more aesthetic in the absence of pathologies, whereas in gingivectomy, it would be for excision of the gums with the pathology.